BAHASA UPDATE FOR DOCTORS a compilation of articles from Berita MMA - Edariah Abu Bakar (Trafford, 2013)
Bahasa Update for Doctors is a compilation of articles on Medical Terminology in Bahasa Malaysia which were published in 1991-92 in Berita M.M.A., a monthly newsletter of the Malaysian Medical Association. With a sprinkling of humor here and there, the author updates doctors and other health professionals on the dynamic development of medical terms in Bahasa. Her light approach towards this otherwise-dry subject makes for fun reading and quick referencing of medical terms. Bahasa Update is useful for doctors, nurses, and other health professionals, especially if they are teaching in Bahasa Malaysia, either in total or used bilingually with English.